Analysis and Evaluation of Prospects for the Development of New Drugs Derived from Benzodiazepines - N. Yu. Porseva; F. V. Sobin; A. V. Soloninina; N. A. Pulina; E. R. Kurbatov; O. N. Dvorskaya (Разработка и регистрация лекарственных средств)
Introduction. The use of drugs derived from benzodiazepine for the treatment of various diseases continues to be relevant. Benzodiazepines are approved by most regulatory authorities around the world. Despite the large number of side effects and non-medical use, they are becoming more promising in emergency care for prolonged seizures and epileptic status.Aim. To analyze the existing medicines on the market of the Russian Federation based on benzodiazepine derivatives and assess the prospects for development in this direction.Materials and methods. The study was conducted on the basis of regulatory legal acts in the field of healthcare and the circulation of medicines, publications of Russian and foreign authors, the results of scientific research using situational, comparative, structural-logical and content analysis methods. The information base of the study was the online database "State Register of Medicines" (grls.minzdrav.gov.ru), databases of peer-reviewed publications: PubMed and Scopus.Results and discussion. Data were obtained on the range of medicines derived from benzodiazepines according to the following indicators: international nonproprietary names, trade names, medicines, manufacturing countries and enterprises, dosage forms. The problem of "medicinal sovereignty" is discussed. Promising niches have been found for the development of innovative drugs derived from benzodiazepines.Conclusion. It has been established that mainly domestic benzodiazepine-type drugs are represented on the Russian pharmaceutical market, while there is a certain shortage of pharmaceutical substances. In Russia, such dosage forms as films, transdermal plasters and preparations for the inhalation use of benzodiazepine derivatives are not registered. It is important to create innovative dosage forms capable of providing a fast, non-invasive and socially acceptable method of use and a high rate of adherence to treatment by patients.